PENGARUH KUALITAS PELAYANAN DAN PENANGANAN ADUAN TERHADAP KEPUASAN PENGGUNA BUS RAPID TRANSIT (BRT) TRANSJAKARTA KORIDOR 1 BLOK M- KOTA - Rivalin Arshanda; R. Slamet Santoso (Journal of Management and Public Policy, 2026)
The Greater Jakarta Metropolitan Area is a center of economic activity with a high level of population mobility, making public transportation modes such as the TransJakarta Bus Rapid Transit (BRT) the primary choice for commuters. TransJakarta Corridor 1 (Blok M - Kota) is one of the busiest routes with a continuously increasing number of users in line with the growth of the urban population in Jakarta. However, the increase in the number of users is not always matched by user satisfaction, which is influenced by suboptimal service quality and user complaints on social media that indicate a lack of responsiveness from the operator in handling complaints. This study aims to analyze the effect of Service Quality (X1) on User Satisfaction (Y), the effect of Complaint Handling (X2) on User Satisfaction (Y), and the simultaneous effect of Service Quality (X1) and Complaint Handling (X2) on User Satisfaction (Y) among TransJakarta BRT Corridor 1 users. This study uses a quantitative explanatory approach, collecting data through questionnaires, documentation, and interviews with TransJakarta BRT users based on proportional random sampling techniques involving 100 respondents spread across Corridor 1 (Blok M - Kota) bus stops. The analysis techniques used include the Spearman Rho validity test, Cronbach's Alpha reliability test, Kendall Tau (τ) correlation, Kendall Concordance (W), and Coefficient of Determination (R²). The analysis techniques used were Spearman's rho validity test, Cronbach's alpha reliability test, Kendall Tau (τ) correlation, Kendall Concordance (W), and Coefficient of Determination (R2). The results show a positive and significant relationship between Service Quality (X1) and User Satisfaction (Y) of 0.633, with the coefficient of determination contributing 59.9%. The correlation of other variables shows that there is a positive and significant relationship between Complaint Handling (X2) and User Satisfaction (Y) of 0.580 and a coefficient of determination of 48.8%. Simultaneously, there is a positive relationship between Service Quality (X1) and Complaint Handling (X2) with User Satisfaction (Y) of 0.998 and a coefficient of determination of 60.3%. This study is expected to provide an overview of the relationship between service quality and complaint handling with user satisfaction, as well as provide recommendations for TransJakarta operators to improve services in Corridor 1.